Spiritualitas Kristen di Era Pandemi Covid-19 - Siburian, Ramsida (Sekolah Tinggi Diakones HKBP, 2021)
This article describes the impact of covid-19 for the life of Christian spirituality which has affected all sectors such as economy, education and health. To answer the problem in this article, the authors used study of literature in accordance with the topic of writing. The findings of this article is that the outbreak of Covid-19 has affected Christian spirituality.